Idursulfase Beta (Hunterase) Therapeutic Experience in a Patient with Mucopolysaccharidosis Type II - Nato D. Vashakmadze; Nataliya V. Zhurkova; Ekaterina Yu. Zakharova; Ludmila K. Mikhaylova; Marina A. Babaykina (Вопросы современной педиатрии)
Background. Mucopolysaccharidosis type II (MPS II, Hunter syndrome) is an X-linked recessive disease caused by lysosomal enzyme iduronate-2-sulfatase deficiency resulting in progressive glycosaminoglycans (GAG) accumulation in tissues (dermatan sulfate and heparan sulfate). GAG accumulation in cells leads to the development of progressive pathological disorders, malfunction of various organs and systems, early disability, and decrease in life expectancy. Enzyme replacement therapy (ERT) reduces the rate of life-threatening conditions development in patient. ERT would be more effective if it is prescribed early, especially at preclinical stage. This is the time when there are no severe irreversible changes in the cell, thus, pathogenetic therapy will decrease GAG accumulation in lysosomes, slow down the pathological process, and improve patient's condition. Clinical case description. Male patient diagnosed with MPS II was administrated with ERT idursulfase beta at the age of 6 months. It led to milder disease course compared to proband uncle who had similar mutation in the IDS gene, severe disease phenotype, and later initiation of ERT (at the age of 2.5 years). Conclusion. Early ERT initiation in patients with MPS II significantly slows down development of severe and life-threatening complications, increases the duration and improves the quality of life.